TRANSLATING POETRY ON E-LEARNING DISCUSSION FORUM; STUDENTS’ LEXICAL CHOICES AND CULTURAL ORIENTATIONS - Afriliani Afriliani (Universitas Muhammadiyah Gorontalo, 2022)
AbstractTranslating poetry in the distance learning ecosystem provides students the opportunity to learn through an online discussion forum called E-Learning. Students are given the task of translating poetry and leaving comments on the work of other students. This article compares three translations of the poem entitled